Proceedings of the 2019 4th International Conference on Social Sciences and Economic Development (ICSSED 2019) 2019
DOI: 10.2991/icssed-19.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Improving Makers’ Remix Contribution Behavior in the Open Innovation Communities——An Example of Thingiverse

Abstract: Using existing innovations as raw materials or inspiration to promote further innovation is becoming a new way of knowledge reuse and contribution in open innovation community (OIC). Study on makers' remix contribution behavior in the open innovation communities will help to promote the development of community innovation based on remix. Based on the theories of social capital, pro-social behavior and psychological ownership, this paper studies how social network relationship, norm of reciprocity, self-rated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…We bridge this gap by formulating a nonlinear human-AI co-design framework featuring flexible communication and selective choices. Following the nonlinear framework, Opti-Muse enables parallel iteration [21] and remixing [7,46,58,63]. Similar to Rezwana's finding in Penpal [53], we observe enhanced user engagement in OptiMuse, where AI was perceived as more collaborative than a mere tool.…”
Section: Discussion 61 Nonlinear Design For Co-creative Systemssupporting
confidence: 80%
See 2 more Smart Citations
“…We bridge this gap by formulating a nonlinear human-AI co-design framework featuring flexible communication and selective choices. Following the nonlinear framework, Opti-Muse enables parallel iteration [21] and remixing [7,46,58,63]. Similar to Rezwana's finding in Penpal [53], we observe enhanced user engagement in OptiMuse, where AI was perceived as more collaborative than a mere tool.…”
Section: Discussion 61 Nonlinear Design For Co-creative Systemssupporting
confidence: 80%
“…Many design tools allow designers to merge their human collaborators' ideas into their creative output iteratively [5,12,39]. Also, there has been a surge in research interest in exploring methods to foster innovative remixing [7,46,58,63]. For instance, through an empirical study on the Thingiverse (a 3D printing community), Tan et al [58] revealed the contradictory impact of knowledge endowment heterogeneity on users' quality and quantity of remixing.…”
Section: Collective Creativitymentioning
confidence: 99%
See 1 more Smart Citation